2016
DOI: 10.1039/c5ay03003j
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of four vasoactive phytochemicals in different pharmaceutical preparations by a simple HPLC-DAD method

Abstract: A new, simple isocratic HPLC method was developed and validated for the simultaneous estimation of four vasoactive phytochemicals: ascorbic acid (ASC), rutin (RUT), hesperidin (HSP), and diosmin (DSM) in different pharmaceutical preparations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In this case, chromatography with different types of detectors is the most often applied method for its identification and determination with high selectivity and acceptable sensitivity. High-performance liquid chromatography (HPLC) with UV- [5][6][7][8], diode-array [9,10] and tandem massspectrometric [11][12][13] detection is usually applied for these purposes. Recently, several approaches based on ultra-HPLC with tandem mass-spectrometric detector [14,15] and high-performance thin-layer chromatography with UV- [16] and densitometric [17] detection have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, chromatography with different types of detectors is the most often applied method for its identification and determination with high selectivity and acceptable sensitivity. High-performance liquid chromatography (HPLC) with UV- [5][6][7][8], diode-array [9,10] and tandem massspectrometric [11][12][13] detection is usually applied for these purposes. Recently, several approaches based on ultra-HPLC with tandem mass-spectrometric detector [14,15] and high-performance thin-layer chromatography with UV- [16] and densitometric [17] detection have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, promising therapeutic prospects for the treatment of PC include phytochemicals, which are naturally occurring alternatives to androgens generated by a wide variety of plants [7, 8]. A phytochemical compound found in grapes, peanuts, and berries called resveratrol (RES) is among the appealing ones.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] A through literature survey revealed that various analytical and few bioanalytical methods were published to describe the quantification of Ethamsylate and Tranexamic acid in active pharmaceutical ingredient and pharmaceutical dosage forms to study the purity, degradation products by UV-Spectrophotometric method. [5][6][7][8] and RP-HPLC [9][10][11][12][13][14][15] . Our literature survey also revealed that there was no method till date reported using UPLC at nanogram level of lower quantification and identification concentration for these principle components within the short period of time with the good resolution and peak shape.…”
Section: Introductionmentioning
confidence: 99%